1999
DOI: 10.1111/j.1834-7819.1999.tb00228.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of polymerized commercial cyanoacrylate adhesive on cultured human oral fibroblasts

Abstract: Cyanoacrylate (CA) has been used as both a commercial and tissue adhesive. Dentists may have had the experience of patients repairing their own acrylic‐based dentures using a cyanoacrylate (CA) adhesive known as ‘super glue’. This study evaluated the cytotoxicity of commercial CA adhesives when fully polymerized, as well as the toxicity of substances released from polymerized commercial CA adhesives after incubation of these materials for various periods of time. Toxicity was tested on cultured oral fibroblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 18 publications
1
36
0
2
Order By: Relevance
“…This recent study also found that, while the cytotoxicity of commercial CA is reduced considerably following incubation with the media for 24 h, it still releases cytotoxic substances for at least 2 wk 20) . Similar results were found with various commercially available CA adhesives 20) . Earlier work has proposed that CA adhesives may generate lipid hydroperoxides that activate prostaglandin and thromboxane biosynthesis and also oxidise and lyse cell membranes 21) .…”
Section: Cytotoxicitymentioning
confidence: 82%
See 2 more Smart Citations
“…This recent study also found that, while the cytotoxicity of commercial CA is reduced considerably following incubation with the media for 24 h, it still releases cytotoxic substances for at least 2 wk 20) . Similar results were found with various commercially available CA adhesives 20) . Earlier work has proposed that CA adhesives may generate lipid hydroperoxides that activate prostaglandin and thromboxane biosynthesis and also oxidise and lyse cell membranes 21) .…”
Section: Cytotoxicitymentioning
confidence: 82%
“…The polymerisation or setting reaction of CA is exothermic and the heat released may cause cell damage in cell culture and possibly when used as a tissue adhesive or whenever CA comes into direct contact with cells 1) . Even when filter paper is used as the vehicle for the adhesive to avoid direct cell contact with the adhesive, this form of polymerised commercial CA has been found to be cytotoxic to human oral fibroblast cell culture 20) . This recent study also found that, while the cytotoxicity of commercial CA is reduced considerably following incubation with the media for 24 h, it still releases cytotoxic substances for at least 2 wk 20) .…”
Section: Cytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Cyanoacrylates have not been reported in association with development of malignancy. However, direct toxicity of these molecules reported includes urticaria, contact dermatitis, and other dermatoses [2, 3]. Additionally, reports have been published regarding development of chronic granulomatous reactions to cyanoacrylate administration [4].…”
Section: Discussionmentioning
confidence: 99%
“…8,13,14 A toxicidade destes adesivos está relacionada a sua velocidade de degradação, e ao tamanho da cadeia, ou seja, quanto maior for a cadeia lateral, menor a velocidade de degradação e menor a histotoxicidade, e também, quanto maior a cadeia lateral maior tempo de cura. 13,14 Vários autores ao longo dos anos analisaram a biocompatibilidade dos adesivos de cianoacrilato, 14,15 e observaram que o metil-cianoacrilato é o que apresenta o maior grau de histotoxicidade, causando edema e necrose tecidual, sendo contraindicados para o uso clínico. 16 Adesivos de etil-cianoacrilato não apresentaram reação inflamatória, apesar de apresentarem uma maior velocidade de degradação.…”
Section: Introductionunclassified